Study of the Compositional, Microbiological, Biochemical, and Volatile Profile of Red-Veined Cheese, an Internal Monascus-Ripened Variety - Jiao, Jingkai; Zheng, Zhiqiang; Liu, Zhenmin; You, Chunping (Frontiers in Nutrition, 2021)
Red-Veined Cheese is an experimental internal mold-ripened cheese using red koji powder as the red starter. The objective of this study was to characterize the physicochemical parameters, microorganisms, proteolysis, lipolysis, and volatile profile of the cheese during 33 days of ripening. The gross composition was 56.66% (w/w) for total solids, 45.8% (w/w) for fat-in-dry matter, 2.58% (w/w) for salt content and 37.8% (w/w) for protein. The pH increased from 4.88 to 5.23 during ripening. The Monascus den-sity first rose and then fell, while total mesophilic bacteria count declined steadily throughout the maturation. Proteolysis de-gree in experimental group was significantly higher than in control group without inoculation of red koji powder. Analysis of the fatty acid profile showed that the internal Monascus-fermentation also promoted lipolysis. A total of 63 volatile compounds, including 12 ketones, 14 alcohols, 15 acids, 13 esters, 5 aldehydes, 3 lactones and 1 phenol, were identiﬁed by gas chromatog-raphy-mass spectrometry (GC–MS) coupled with headspace solid-phase microextraction (HS-SPME). The main chemical groups of volatile compounds were ketones, alcohols, acids and esters whereas aldehydes, lactones, and phenols represented only minor components. At the end of ripening, the levels of ketones, alcohols, esters were significantly higher in the experimental cheese compared with the control. Our results therefore show that the internal Monascus-fermentation is not only a suitable technology to form red veins in the paste but also an effective method to impact the composition of volatile compounds in cheese, which can thus distinguish it from other internal mold-ripened cheeses and surface-ripened Monascus-fermented cheese